2010
DOI: 10.1007/s00122-010-1305-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, inter-gene pool introgression and nutritional quality of common beans (Phaseolus vulgaris L.) from Central Africa

Abstract: The Great Lakes region of Central Africa is a major producer of common beans in Africa. The region is known for high population density and small average farm size. The common bean represents the most important legume crop of the region, grown on over a third of the cultivated land area, and the per capita consumption is among the highest in the world for the food crop. The objective of this study was to evaluate the genetic diversity in a collection of 365 genotypes from the Great Lakes region of Central Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
211
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(250 citation statements)
references
References 38 publications
24
211
2
13
Order By: Relevance
“…These results from Tanzania confirm previous findings indicating that both Andean and Mesoamerican beans are grown within some African countries (Wortmann et al, 1998;Mahuku et al, 2002). In Tanzania, it has been found that farmers grow both Andean and Mesoamerican beans and in most cases they mix the two together in the same plot of land as a strategy of risk management since some cultivars fail and others are tolerant to biotic and abiotic factors (Blair et al, 2010).…”
Section: Host Genotype Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…These results from Tanzania confirm previous findings indicating that both Andean and Mesoamerican beans are grown within some African countries (Wortmann et al, 1998;Mahuku et al, 2002). In Tanzania, it has been found that farmers grow both Andean and Mesoamerican beans and in most cases they mix the two together in the same plot of land as a strategy of risk management since some cultivars fail and others are tolerant to biotic and abiotic factors (Blair et al, 2010).…”
Section: Host Genotype Characterizationsupporting
confidence: 88%
“…In other regions of Tanzania, beans are consumed mostly with rice and maize meal for which the preference is large seeded beans in these dishes. In studies in countries neighboring Tanzania, the proportion of production of Andean and Mesoamerican bean in Uganda (Okii et al, 2014) is similar to that of Tanzania, while in Rwanda, common beans of Mesoamerican origin outnumbered the Andean ones (Blair et al, 2010).…”
Section: Host Genotype Characterizationmentioning
confidence: 94%
“…The atomic absorption spectrophotometer (AAS) method has been suggested for routine estimation of Fe and Zn in seeds (Sahrawat et al 2002;Blair et al 2009bBlair et al , 2010aBlair et al ,b,2011). An excellent review on the role of atomic spectrometry in plant science has been published elsewhere, and it is important to recognize recent developments in multielemental and speciation analyses in plants with the resulting functional roles of different elements in plant science ).…”
Section: Phenotypic Screensmentioning
confidence: 99%
“…Similarly, the transport of iron in phloem is well studied although the transport mechanism is not well known and may involve citric acid conjugates and/or nicotianamine as a transport system with most of the studies on Fe-transport based on mutants in peas (Grusak 2000(Grusak , 2002 or Arabidopsis (Grotz and Guerinot 2006), or rice (Takahashi et al 2001;Cheng et al 2007;Masuda et al 2009). Iron-uptake through iron reductase activity (IRA) seems to be important for total seed accumulation of this mineral in common bean (Blair et al 2010a).…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
“…Mesoamerican and Andean common bean seeds have a large genetic variability for iron, and values from 29 to 159 mg kg -1 dry matter (DM) have been reported Blair et al, 2010aBlair et al, , 2010bJost et al, 2013;Ribeiro et al, 2014aRibeiro et al, , 2014b, which allows for the selection and use of iron-rich cultivars for human consumption.…”
Section: Introductionmentioning
confidence: 99%